Feedback‐dependent neuronal properties make focal dystonias so focal. (31st August 2020) - Sedov, Alexey; Usova, Svetlana; Popov, Valentin; Tomskiy, Alexey; Jinnah, Hyder A.; Shaikh, Aasef G.
Abstract: Focal dystonia, by definition, affects a specific body part; however, it may have a widespread neural substrate. We tested this hypothesis by examining the intrinsic behaviour and the neuronal properties that are modulated by changes in the physiological behaviour of their connections, that is feedback dependence, of the isolated pallidal neurons. During deep brain stimulation surgery in 12 patients with isolated cervical dystonia (without hand involvement), we measured spontaneous as well as evoked single‐unit properties in response to fist making (hand movement) or shoulder shrug (neck movements). We measured the activity of isolated neurons that were only sensitive to the neck movements, hand movement, or not responsive to hand or neck movements. The spontaneous firing behaviour, such as the instantaneous firing rate and its regularity, was comparable in all three types of neurons. The neck movement‐sensitive neurons had prominent bursting behaviour in comparison with the hand neurons. The feedback dependence of the neck movement‐sensitive neurons was also significantly impaired when compared to hand movement‐sensitive neurons. Motor‐evoked change in firing rate of neck movement‐sensitive neurons rapidly declined; the decay time constant was much shorter compared to hand movement‐sensitive neurons. These results suggest that in isolated cervical dystonia, at the resolution of single neurons, the deficits are much widespread, affecting the neurons that drive the neck movement as well as the hand movements. We speculate that clinically discernable dystonia occurs when additional abnormality is added to baseline dysfunctional network, and one source of such abnormality may involve feedback. Abstract : We measured the activity of isolated neurons that were only sensitive to the neck movements, hand movement, or not responsive to hand or neck movements. The spontaneous firing behaviour was comparable in all three types of neurons. The neck movement‐sensitive neurons had prominent bursting behaviour in comparison with the hand neurons. The feedback dependence (time constant) of the neck movement‐sensitive neurons was also significantly impaired when compared to hand movement‐sensitive neurons.